Etiological factors and maternal outcome in pregnancies with malpresentation: an observational study - Shruthi, S.; Apollo, A. Anisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The most common presentation of the fetus is malpresentation. These include breech, face, brow, shoulder and compound presentations. Malpresentations of fetus complicate labor in about 5% of pregnancies. To find out the incidence of malpresentation, to analyze etiological factors of malpresentation, to evaluate the maternal outcome in cases with a malpresentation. Methods: This prospective observational study was done in, Chengalpattu Government medical college and hospital. Study period from October 2018 to September 2019. Pregnancies with malpresentation presenting to the department of obstetrics and gynecology at CMCH were included in the study. Results: A total of 680 malpresentation were admitted in this period were included in this study. The incidence of malpresentation during the study period was 7.72%. The incidence of the breech was 4.38%, transverse lie 1.11%, face 0.28%, brow 0.05% and compound presentation 0.13%. The common causes were prematurity, multiple gestations, grand multiparty, IUGR, oligohydramnios, anomalies of uterus, polyhydramnios, contracted pelvis, placenta previa, hydrocephalus, prematurity was reported as the commonest cause of breech presentation and multiparty for transverse lie, face and brow presentations. The most common complication was obstructed labor 6.9% followed by post-partum hemorrhage 3.65%. There was no maternal death due to malpresentation during the period of study. Conclusions: Early diagnosis and timely management can prevent the complications of labor associated with a malpresentation. Delivery should be planned at centers which have expertise in conducting vaginal delivery in malpresentation with good intrapartum monitoring and with facilities for cesarean section for the better feto-maternal outcome.